Psychometric validation of the Spanish version of the Dundee Ready Education Environment Measure applied to dental students. (13th December 2013) - Tomás, I.; Casares‐De‐Cal, M. A.; Aneiros, A.; Abad, M.; Ceballos, L.; Gómez‐Moreno, G.; Hidalgo, J. J.; Llena, C.; López‐Jornet, P.; Machuca, M. C.; Monticelli, F.; Palés, J.
Abstract Aim To carry out a psychometric evaluation of the Spanish‐language version of the Dundee Ready Education Environment Measure (DREEM) applied to dental students. Methods A total of 1, 391 students from nine Spanish public schools of dentistry responded to the DREEM questionnaire. To analyse the reliability of the DREEM questionnaire, the internal consistency was assessed and a 'test‐retest' carried out. Validity was evaluated through analysis of item response rate, floor and ceiling effects, corrected item‐total and item‐subscale correlations and factor structure. A confirmatory factor analysis was performed to analyse the structure of the original DREEM scale. Results Cronbach's alpha coefficient for the 'Educational Climate' (EC) global scale was 0.92. In the subscales, the 'observed' Cronbach's alpha coefficients ranged between 0.57 and 0.79 and were higher than the 'expected' ones; except for the Social subscale. In the DREEM questionnaire, all of the corrected correlation coefficients between the items and the EC global scale, and the items and their corresponding subscales, were >0.2; except for items 50 and 17. All goodness‐of‐fit indices of confirmatory factor analysis showed acceptable values (close to one or zero, depending on the case), and there was consistency in the results. Conclusions The Spanish‐language version of the DREEM questionnaire is a reliable and valid instrument for analysing the EC for dental students and its factor structure is supported by the data. Although our findings indicate that the DREEM may be as culturally independent as was originally stated, more research should be directed at verifying the factor structure in various languages and cultural environments.